REVISI DAN UJI PEMBELAJARAN DESAIN INSTRUKSIONAL DIKLAT JARAK JAUH ONLINE PENELITIAN TINDAKAN KELAS DI BALAI DIKAT KEAGAMAAN JAKARTA - Asip Suryadi (Balai Diklat Keagamaan Jakarta, 2020)
This study aims to develop instructional system of Classroom Action Research Online Distance Training at BDK Jakarta. This development research uses the Borg, Borg and Gall models. This research is a part of the research and development series, namely the product revision step and the use test. The revised results a simpler curriculum structure and learning activities. Furthermore, the instructional design was tested to 80 participants and data showed that training participants were no longer trapped at the beginning of the program and could continue to follow the program easily, resulting in an increase in the percentage of graduation from before the revision was only 24% after the revision to 71.42%. However, instructional improvements have not been able to improve retention. This study recommends continuing instructional designs development so that the instructional design can improve both the percentage of graduation and retention.